Efficacy of Native Bacillus thuringiensis against Mosquito Vector - GC , Ganga; Parajuli, Kshama; Gautam, Ishan; Banjara , Megha Raj; Ghimire , Prakash; Rijal, Komal Raj (Journal of Nepal Health Research Council, 2024)
Background: Larval source management is an effective measure to control mosquito-borne diseases. Bacillus thuringiensis produces specific insecticidal crystal proteins toxic to mosquito larvae. In many parts of the South East Asian region, Bacillus thuringiensis is used for larval source management. In Nepal, larvicidal Bacillus thuringiensis is not available. The study aims to isolate larvicidal Bacillus thuringiensis from soil samples of Nepal to control mosquitoes. Methods: Native Bacillus thuringiensis was obtained from soil samples by the acetate selection method. It was identified by observing crystal protein with Coomassie Brilliant Blue stain in a light microscope. The mosquito larvae were collected from different breeding habitats. A preliminary bioassay was performed by inoculating three loopful of 48 hours culture of spherical crystal protein producing Bacillus thuringiensis in a plastic cup containing 25 larvae and 100 ml of sterile distilled water. The cup was incubated at room temperature for 24 hours to observe the mortality of larvae. Further selective bioassay was performed with the isolate which showed 100% mortality, as described above in four replicates along with the negative and positive control. Results: Out of 1385 Bacillus thuringiensis obtained from 454 soil samples, 766 (55.30%) were spherical crystal protein producers, among them, a single strain (14P2A) showed 100% mortality against mosquito larvae. The lethal concentration doses required to kill 50% and 90% of the larval population were 32.35 and 46.77 Parts per million respectively. Conclusions: The native Bacillus thuringiensis produces the crystal protein effective in killing mosquito larvae. The native Bacillus thuringiensis should be included as a tool to control mosquito-borne diseases in Nepal. Keywords: Bacillus thuringiensis; mosquito; Nepal; tool.